Effect of Infill Wall Opening Ratio on the Mechanical Characteristics of Reinforced Concrete Frames - Pham, Phu-Anh-Huy; Le, Cao-Vinh; Nguyen, Van-Tien (Salehan Institute of Higher Education, 2025)
This study investigated the influence of infill wall (IW) opening ratios on the mechanical performance of reinforced concrete (RC) frames using a novel numerical model. The proposed model incorporated stiffness degradation and a nonlinear